The spatial relationship and influence mechanism of traditional villages and intangible cultural heritage: a case study of the upper reaches of the Yellow River Basin - Qianming Xue; Yuehao Huang (Humanities & Social Sciences Communications)
Abstract This paper focuses on 262 traditional villages (TVs) and 189 nationally recognized intangible cultural heritage (ICH) items in the upper Yellow River basin (YRB). Using nuclear density, distribution equilibrium and other research methods., this paper tries to reveal the spatial relationship between TVs and ICH, and analyzes its influencing factors. Through an analysis of influencing factors, the study identifies pathways for their integrated development. The findings are as follows: (1) There are significant differences in the spatial distribution of TVs and ICH in the upper YRB. TVs exhibit a “multi-core aggregation, dispersed concentration” pattern, with a high degree of imbalance at the provincial (or autonomous region) level. In contrast, ICH shows a “sparse south, dense center, and sparse north” distribution, with a lower degree of imbalance at the provincial level. (2) Although there is generally a high degree of spatial alignment between TVs and ICH, but at the provincial (or autonomous region) level, three types of regional displacements have been identified: high positive displacement, low positive displacement, and high negative displacement. (3) Factors such as altitude, river systems, temperature conditions, regional economy, accessibility, population density, urbanization rate, cultural characteristics, and funding policies significantly influence the spatial distribution of TVs and ICH. urbanization rate has a common influence and explanatory power on the spatial distribution of both TVsand ICH in the YRB, with altitude, financial policies, cultural history, and other factors having secondary influence and explanatory power.These factors are crucial in determining the pathways for their integrated development.